Should women have different ECG criteria for CRT than men?. Issue 1 (July 2017) - Lee, Noel S.; Lin, Felice; Birgersdotter-Green, Ulrika
Abstract: One of the key aspects of heart failure management is whether patients should be considered for device therapy. Clinical trials, which have employed QRS duration and morphology as measures of left ventricular dyssynchrony, have demonstrated the morbidity and mortality benefit of cardiac resynchronization therapy. Women, however, are underrepresented in these trials, the basis of which current guidelines and standards of care are derived. Despite low enrollment of women, several studies highlight the statistically significant improvement in risk reduction that women gain from cardiac resynchronization therapy compared to men. This review discusses the foundation for current guidelines and the building evidence that women may reap more benefit from cardiac resynchronization therapy than men. Given these data, a more individualized approach should be considered in prescribing this device therapy in the future, particularly in women.